Discourse Analysis of Online Religious Message (Case Study: Instagram Pages of Alireza Panahian and Hasan Aghamiri) - ebtasam razavi dinani; vahid aqili; hassan masoudi (Religion & Communication)
Today, due to the widespread influence of modern media and their unique features, we are witnessing the emergence of new arenas in various scientific fields. On the one hand, the profound impact of media such as social networks and on the other hand, the importance of religion as one of the most important phenomena studied in human societies throughout history, highlights more than ever the need to study the effects of media on religion and the importance of discovering existing discourses in this field. Therefore, in this article, the effect of social networks (specifically Instagram as one of the most popular and widely used media) on the religious messages of two influential clergymen (Alireza Panahian and Hassan Aghamiri) is examined. The research data is collected from the Instagram pages of these two individuals over a 6-month period in 2021 and 2022. In this article, by examining theories in the field of religious discourses (such as discourses of Westernism, nationalism and Islamism, discourses of modernism, Shariaism and civilizationism and discourses of intellectualism and religious intellectualism, Islamic tradition and fundamentalism), their summary in the form of discursive dualities in the field of religion is presented as theoretical foundations. The results obtained from discourse analysis in the final stage show that the dominant discourse in Alireza Panahian's religious messages is shaped around "idealism and Islamic civilization". This finding is consistent with the theory of civilizationism in the theoretical foundations section. On the other hand, the dominant discourse governing Hassan Aghamiri's religious messages revolves around "tolerance and criticism of the official religious authority", which is in line with the theory of religious intellectualism.